Determinants of Muscle and Bone Aging. Issue 11 (November 2015) - Curtis, Elizabeth; Litwic, Anna; Cooper, Cyrus; Dennison, Elaine
<x xml:space="preserve">Abstract</x> Loss of bone and muscle with advancing age represent a huge threat to loss of independence in later life. Osteoporosis represents a major public health problem through its association with fragility fractures, primarily of the hip, spine and distal forearm. Sarcopenia, the age related loss of muscle mass and function, may add to fracture risk by increasing falls risk. In the context of muscle aging, it is important to remember that it is not just a decline in muscle mass which contributes to the deterioration of muscle function. Other factors underpinning muscle quality come into play, including muscle composition, aerobic capacity and metabolism, fatty infiltration, insulin resistance, fibrosis and neural activation. Genetic, developmental, endocrine and lifestyle factors, such as physical activity, smoking and poor diet have dual effects on both muscle and bone mass in later life and these will be reviewed here. Recent work has highlighted a possible role for the early environment. Inflammaging is an exciting emerging research field that is likely to prove relevant to future work, including interventions designed to retard to reverse bone and muscle loss with age. J. Cell. Physiol. 9999: 2618–2625, 2015. © 2015 Wiley Periodicals, Inc.